2020
DOI: 10.1155/2020/1283632
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of Immune Checkpoints in Clear Cell Carcinoma of the Uterine Cervix

Abstract: The purpose of this study was to investigate the expression levels of the immune checkpoint proteins, programmed cell death-ligand 1 (PD-L1), B7-H3, B7-H4, and V-domain Ig suppressor of T cell activation (VISTA), as well as the significance thereof, in clear cell carcinoma (CCC) of the cervix (a rare histological subtype of cervical cancer). We also compared the expression statuses of these biomarkers in cervical CCCs with those in cervical squamous cell carcinomas (SCCs). We evaluated the expression of PD-L1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…Immunohistochemistry was performed using our laboratory protocol as described previously. 14 , 17 , 26 Briefly, 4 μm TMA serial sections were deparaffinized and subjected to heat-induced epitope retrieval with 10 mM sodium citrate (pH 6.0) at 95°C for 20 min. The endogenous peroxidase activity was quenched using a 0.3% hydrogen peroxide solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry was performed using our laboratory protocol as described previously. 14 , 17 , 26 Briefly, 4 μm TMA serial sections were deparaffinized and subjected to heat-induced epitope retrieval with 10 mM sodium citrate (pH 6.0) at 95°C for 20 min. The endogenous peroxidase activity was quenched using a 0.3% hydrogen peroxide solution.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed using our laboratory protocol as described previously. 14,17,26 Briefly, 4 https://doi.org/10.2147/OTT.S318082…”
Section: Immunohistochemistry and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Only one study reported the expression of PD-L1 (clone E1L3N) in 50 patients with CCC of the uterine cervix, and found a positive PD-L1 expression in 22% (CPS ≥1) of tumours. 13 Only Rivera-Colon et al evaluated PD-L1 expression using PD-L1 IHC 22C3 pharmDx; PD-L1 expression was observed in 68% cases [HPVA = 87 and HPVindependent = two (PD-L1 expression was positive based on both CPS and TPS)] based on the CPS and in 29% cases based on the TPS. 11 The discrepancy between the results of these investigations can be explained by different study designs, histopathological types and different clones used.…”
Section: Discussionmentioning
confidence: 99%
“…12 There is only one report regarding the expression of PD-L1 in clear cell carcinoma (CCC) of the uterine cervix. 13 One study, including 127 patients with HPVA CA, showed that PD-L1 expression correlated with tumour-infiltrating lymphocytes (TILs). 14 The immune microenvironment and PD-L1 expression in HPV-independent CA are not completely understood.…”
Section: Introductionmentioning
confidence: 99%